The Theory of Change in Law: Al-Syatibi's Philosophy of Law - Sylviah Sylviah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
The conception of change in law is something that cannot be denied, it is caused by the reality of a very complex era. The birth of Islamic thoughts has become its own style in responding to global challenges and at the same time providing scientific treasures in the field of Islamic law. As-Syatibi is a reformer figure in change in law, especially in the dimension of Islamic legal philosophy. Thus, the reflection of this study reveals Al-Syatibi's conception of thinking in the frame of change in law. The method in this study is a conceptual study with a library approach, which examines books and books related to the object of study. The results show that al-Syatibi's philosophical thought of law cannot be separated from the concept of maslahat embodied in maqashid al-syariah by being seated at several levels of urgency, namely dharuruyah, hajjiyah and tahsiniyah. The conceptual framework of Al-Syatibi's thinking in the concept of change in law in achieving benefit. change in law must lead to human empowerment by reducing normativity and by bringing the law closer to its historical dimension.